2021
DOI: 10.3390/ijerph18147288
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Dynamics among Couples Dealing with Breast Cancer: A Systematic Review

Abstract: Most studies have been concerned with the experiences and needs of women with breast cancer and spouses/partners separately. In this review, the relationship dynamics that characterize the couple’s experience of breast cancer treatment were investigated. Findings will inform both researchers and professionals in the area of oncology. A systematic literature search was performed in CINAHL, PsychINFO, MEDLINE, Scopus and Web of Science. A checklist for qualitative and observational studies was used to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
2
12
0
1
Order By: Relevance
“…In younger couples or in relationships where coping strategies are not shared, research has shown higher levels of psychosocial distress following a cancer diagnosis, 38 which negatively correlates to quality of life and cancer-related mortality. 39 Our results are in line with previous findings which suggest that attitudes and health beliefs are highly concordant across couples. 16 While some of this may be attributable to assortative mating, previous longitudinal research suggests that spousal influence itself is associated with health enhancing behaviours.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In younger couples or in relationships where coping strategies are not shared, research has shown higher levels of psychosocial distress following a cancer diagnosis, 38 which negatively correlates to quality of life and cancer-related mortality. 39 Our results are in line with previous findings which suggest that attitudes and health beliefs are highly concordant across couples. 16 While some of this may be attributable to assortative mating, previous longitudinal research suggests that spousal influence itself is associated with health enhancing behaviours.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, participants were married for 25-50 years, indicating high levels of compatibility. In younger couples or in relationships where coping strategies are not shared, research has shown higher levels of psychosocial distress following a cancer diagnosis [38], which negatively correlates to quality of life and cancerrelated mortality [39].…”
Section: Accepted Articlementioning
confidence: 99%
“…The broader context should most likely be acknowledged throughout an intervention or clinical process (e.g., therapy) as patients’ and partners’ thoughts and feelings on the subject may change over time. Overall, these findings are consistent with prior research demonstrating a range of types of changes experienced in the relationships of women with metastatic breast cancer ( Valente et al, 2021 ) and highlight the importance of considering the context of the metastatic diagnosis and the changed overall relationship when addressing sexual concerns for partnered women with MBC.…”
Section: Discussionsupporting
confidence: 88%
“…These areas are crucial not only due to the high prevalence of psychological distress among cancer patient but also due to the consequences of such disorders on overall health [ 59 ]. In fact, considering breast cancer, a much more widespread, well-known and well-studied type of cancer among women, a large volume of literature is available on quality of life [ 60 ], sexuality [ 61 , 62 ] and partner relationships [ 63 , 64 ]. Furthermore, future studies should investigate the psychological aspects of sexual experience, shame, body image, desire and avoidance of desire as well as considering the sexual orientation of patients and the specific needs related to it that may emerge.…”
Section: Discussionmentioning
confidence: 99%